The use of autologous fat grafting in facial and body rejuvenation: efficacy, innovative techniques and complications - Suárez-Fuentes, Sergio M.; Flores-Chávez, Luis A.; Martinez-López, Eduardo M.; Castrejón-Cardona, Christian D.; Menéndez-Goti, Laís L. (International Journal of Research in Medical Sciences, 2025)
Autologous fat grafting has revolutionized facial and body rejuvenation by providing natural, biocompatible, and long-lasting results. This review explores recent advancements in harvesting, processing, and injection techniques, emphasizing their efficacy, safety, and aesthetic outcomes. Fat grafting not only restores volume but also demonstrates regenerative properties due to adipose-derived stem cells (ADSCs), enhancing skin texture and elasticity. Modern methods, such as nanofat grafting, offer promising results for delicate areas and scar treatment. Additionally, fat grafting has gained popularity in body contouring, breast reconstruction, and soft-tissue repair, with reported fat retention rates between 60% and 80%. However, complications like fat necrosis, cyst formation, and partial resorption are not uncommon. Rare but severe risks, such as fat embolism, underscore the need for meticulous technique and careful patient evaluation. This review highlights the importance of patient selection and optimized protocols to achieve consistent outcomes, minimize risks, and explore the regenerative potential of fat grafting for emerging applications in medicine.